Mathematical modelling of drying kinetics of kachri (Cucumis callosus) dried in heat pump dryer - S, Ramyashree; Jain, Sanjay Kumar; Jain, Narendra Kumar; Lakhawat, Shreedhar Singh; Kumar, Arun; Singh, Pradeep Kumar (Journal of Postharvest Technology, 2023)
Drying kinetics of pretreated Kachri (Cucumis callosus) slices of thickness 5 and 10 mm were carried out at temperatures of 40, 50 and 60⁰C in a heat pump dryer. Mass transfer in kachri slices during drying was described using Fick’s model of diffusion with drying taking place in a falling rate period. The drying data obtained were fit to three different semi-theoretical mathematical thin layer drying models to determine the best fit model for drying kachri slices by non-linear regression analysis. The goodness of fit was evaluated based on the highest value of the coefficient of determination (R2) and the lower value of root mean square error (RMSE). The experimental results found that the drying rate and effective diffusivity increased with an increase in temperature whereas decreased with the increase in slice thickness. The value of effective diffusivity ranged from 2.14 × 10-07 to 9.41 × 10-08 m2/s. Page model was found a best fit model for describing the drying behaviour of kachri slices dried in a heat pump dryer.